Student Difficulties in Solving Open-Ended Model Mathematics Problems - Henry Kurniawan; Mewa Zabeta; Krisno Budi Prasetyo (Jurnal Inovasi Matematika, 2023)
This descriptive-qualitative study aims to discover factors that influence students' difficulties in solving non-routine problems. The researchers employed open-ended questions that had previously been developed by researchers, ensuring that they were valid, practical, and had potential effects. The researchers brought up this topic because non-routine questions can help students improve their mathematical skills. The study's approach consisted of three stages: preparation, implementation, and data analysis. The research subjects were 31 eighth-grade students from one of Belitang's junior high schools. Data was gathered through observation, interviews, and testing. Observation was utilized to collect data on the learning process, while interviews were used to understand more profoundly and directly about students' difficulties in addressing non-routine tasks. The test was then administered to assess students' ability to solve non-routine tasks. The data was evaluated qualitatively using descriptive analysis. Based on observation and interview data, several factors contributed to students' difficulty in solving non-routine problems, including the fact that students had never worked on non-routine problems during the learning process in class, and the teacher's book only contained routine problems. In relation to the foregoing, the exam results show that students' ability to solve non-routine problems remains poor, with as many as 58.07% receiving poor grades, 19.35% receiving moderate grades, and only 22.58% receiving good grades. With this research, it is envisaged that teachers will assign numerous non-routine tasks in class in the future, allowing students' mathematical abilities to be thoroughly developed.